Responses of SALAFI and Modern Islamic Boarding School Students to the Establishment of New Islamic-based Political Party - Endro Tri Susdarwono (Jurnal Kawakib, 2022)
Political parties have a very strategic role and position. Political parties play a strategic role as a liaison between the government process and citizens, so that the birth of new political parties is needed. This study aims to provide a description of the responses of students from SALAFI Islamic boarding schools and modern Islamic boarding schools related to the establishment of new political parties based or based on Islam. The approach used in this research is descriptive quantitative by using the Kolmogorov-Smirnov method of hypothesis testing. Based on the comparison between the D value in the table and the calculated D value, the D value is 0.051531. This value is smaller than the D value in the table of 0.315376. This study concludes that the null hypothesis is rejected and accepts the alternative hypothesis which states that the responses given by students from SALAFI Islamic boarding schools are better than the responses given by students from modern Islamic boarding schools regarding the establishment of new Islamic-based political parties. In this condition, it can be concluded that the santri who come from SALAFI Islamic boarding schools are more enthusiastic or more receptive in accepting the formation of a new Islamic-based political party.